Le traitement des enfants et des adolescents sportifs ayant un trouble du déficit d`attentionhyperactivité (TDA-H) - Bader, M. (Schweizerische Zeitschrift für Sportmedizin und Sporttraumatologie, 2012)
Attention deficit/hyperactivity disorder (ADHD) has prevalence between 3% and 7% in childhood and adolescence. 80% of patients have comorbidities: developmental disorder, coordination disabilities, emotional disorder, conduct disorder or oppositional-defiant disorder. Patients with ADHD have also executive difficulty (for instance attention regulation, inhibition, working memory, planning and organization). Treatment of ADHD includes a combination of multimodal modalities including drugs, psychotherapy and psychosocial. Stimulants treatments for young ADHD athletes need regular monitoring checking efficient dose and effects on ADHD symptoms and side effects. The physician has to keep in mind risk of abuse drug intake, especially by young sportsman of elite subjected to pressures of results. Atomoxetine (ATX/Srattera®) is now second choice drug since approval by the FDA in december 2002. This drug is a non stimulant medication with noradrenergic action over 24 hours and without risk of abuse. ATX may be particularly useful for some young athletes with ADHD as alternative to stimulants. More researches are needed to explore specific effects of stimulants and atomoextine for athletes with ADHD regarding clinical profiles and taking into consideration the kind of sport that is practised.